QUEST TECHNOLOGY AND ITS DIDACTIC POTENTIAL (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article provides a comprehensive analysis of the role of quest technology in modern education in enhancing students’ cognitive activity, developing their thinking, and fostering collaboration, creativity, and communication competencies. The study explores in depth the psychological and pedagogical foundations of quest technology, its didactic potential, and its practical implementation in teachers’ professional activities. Based on national and international experiences, quest technology is evaluated as an effective educational tool that increases students’ learning motivation, improves the emotional atmosphere of the classroom, and promotes independent thinking and cognitive growth.